2005
DOI: 10.1111/j.1365-2427.2005.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Benthic–pelagic coupling in the population dynamics of the harmful cyanobacterium Microcystis

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
111
3
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 45 publications
5
111
3
4
Order By: Relevance
“…Compared to colonial Microcystis, the cell number of unicellular Microcystis had a significant decrease, suggesting that colonial Microcystis can survive a longer period under the stress of darkness and low temperature than unicellular Microcystis. This may be an explanation why Microcystis colonies were found in winter at the bottom of freshwater lakes (Reynolds et al, 1981;Tsujimura et al, 2000;Brunberg & Blomqvist, 2002;Latour et al, 2004a;Verspagen et al, 2004Verspagen et al, , 2005. Our previous study also indicated that colonial Microcystis exhibited more tolerance to copper than unicellular Microcystis (Wu et al, 2007), supporting that higher endurance to environmental stresses might play an important role in survivals of colonial Microcystis.…”
Section: Discussionsupporting
confidence: 48%
“…Compared to colonial Microcystis, the cell number of unicellular Microcystis had a significant decrease, suggesting that colonial Microcystis can survive a longer period under the stress of darkness and low temperature than unicellular Microcystis. This may be an explanation why Microcystis colonies were found in winter at the bottom of freshwater lakes (Reynolds et al, 1981;Tsujimura et al, 2000;Brunberg & Blomqvist, 2002;Latour et al, 2004a;Verspagen et al, 2004Verspagen et al, , 2005. Our previous study also indicated that colonial Microcystis exhibited more tolerance to copper than unicellular Microcystis (Wu et al, 2007), supporting that higher endurance to environmental stresses might play an important role in survivals of colonial Microcystis.…”
Section: Discussionsupporting
confidence: 48%
“…To our knowledge, this is the first report on microbial communities associated with buoyant Microcystis colonies, which would take an important role during the next summer bloom (Verspagen et al, 2005), during the decline period of annual freshwater bloom. qRT-PCR revealed a gradual decrease in the ratio of bacteria associated with Microcystis colonies, indicating that Microcystis colonies remaining buoyant on the water surface are resistant to bacterial colonization.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the in situ observation that the population density of Microcystis species in the water increased with water temperature. The upward movement of Microcystis species is obviously regulated by cell buoyancy, and some researchers have suggested a positive effect of temperature on the recovery of buoyancy in Microcystis colonies or an increase in the number of buoyant colonies (Thomas & Walsby 1986, Tsujimura et al 2000, Brunberg & Blomqvist 2003, Verspagen et al 2005. Therefore, Microcystis colonies in the sediment are probably stimulated to become active quickly in response to an increase in temperature.…”
Section: Discussionmentioning
confidence: 99%